Insect Meal (Tenebrio molitor) Has High Nutrient Digestibility for Newly Weaned Piglets - Pereira, Juliana Carolina [UNESP]; da Silva, Alan Roberto Alves [UNESP]; Rossiti, Bernardetti Cajaíba Oliveira [UNESP]; da Silva, Rodrigues [UNESP]; da Silva, Letícia Garbin Ribeiro [UNESP]; Evangelista, Mariane Zabotto [UNESP]; dos Santos Ruiz, Urbano; Tse, Marcos Livio Panhoza [UNESP] (Wiley, 2025)
This study aimed to evaluate the inclusion of insect larvae meal (Tenebrio molitor) on the apparent total digestibility of dry matter (DM), gross energy (GE), ether extract (EE), crude protein (CP), neutral and acid detergent fiber (NDF and FDA), and the apparent and standardized ileal digestibility of amino acids (Exp.1) and to evaluate the inclusion of insect meal with iron and manganese supplementation on growth performance and serum hemoglobin concentration by collecting blood (day zero), on the 14th and 32nd days of the experiment (Exp.2). The standardized ileal digestibility values for amino acids and crude protein of insect meal were similar to those found for soybean meal, with high metabolizable energy values (Exp.1), and there was no difference in performance for any of the variables analyzed (p ≥ 0.05) in any of the periods (Exp.2). For serum hemoglobin values, there was no interaction (p ≥ 0.05) between the treatments used and the collection days; however, hemoglobin values increased (p < 0.05) at each collection time. It can therefore be concluded that insect meal for pigs can be considered an alternative ingredient to soybean meal as a source of protein in piglet nutrition due to high digestibility of amino acids without deleterious effect on productive performance.
Keywords: digestibility; performance; pigs; protein source